SEJARAH LINGKUNGAN SEBAGAI PENDIDIKAN PENGURANGAN RESIKO BENCANA DI KABUPATEN KETAPANG KALIMANTAN BARAT - Basuki Wibowo; Agus Dediansyah (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT The learning of environmental history developed in Ketapang District can be utilized as an education for natural disaster risk reduction. This study aims to determine and explore the history of the environment and the potential contained in oral history to be made as a disaster risk reduction education in Ketapang Regency, West Kalimantan. This study uses qualitative research methods with a form of embedded case study strategies. Data sources used are informants, places and events, and documents. Data collection techniques using direct observation techniques, in-depth interviews, and document studies. The sampling technique used is purposive sampling. Data validity uses triangulation and data analysis techniques use interactive analysis techniques. The Potential of Environmental History as Disaster Risk Reduction Education (PPRB) in Ketapang Regency, West Kalimantan is very large. Utilization of history known to the community from its environment will form its own memory. Disaster Risk Reduction Education (PPRB) is oriented to the development of a community and is active, creative, innovative, effective. Through learning the history of the environment will form the character of people who have environmental concerns so that the risk of natural disasters due to environmental damage can be overcome and minimized. Keywords: Environmental history, Disaster Risk Reduction